DAYTON AND POST-DAYTON CONCEPT OF THE ADMINISTRATIVE POWER IN BOSNIA AND HERZEGOVINA ‒ TWENTY FIVE YEARS AFTER DAYTON PEACE AGREEMENT - Vranjes, Nevenko D. (Politeia, 2021)
The Dayton Peace Agreement of 1995 established today’s Bosnia and Herzegovina as a multiple, complex, specific, and unique state with international legal subjectivity with regard to state law, constitutional law, and administrative law. As a result, the form of socio-political order such as it exists in Bosnia and Herzegovina is unknown in modern political systems.From the initial minimum competences granted to state-level institutions as regulated by the Dayton Constitution, there have been, over the course of twenty-five years, significant amendments made in this respect.  With the intervention of the Office of the High Representative (OHR) into the constitutional and legal framework, and, to a lesser extent, by consensual transfer of jurisdiction from the entity level to the state level, administrative capacities of Bosnia and Herzegovina have been strengthened in organisational and functional terms, thus significantly derogating the respective administrative authority of the entities of the Republic of Srpska and the Federation of Bosnia and Herzegovina. This is accompanied by strong hyperinflation of the administrative bodies and organisations at the state level, mostly of unstable legitimacy, which, along with the existence of administrative structures at the remaining thirteen levels of government, classifies the post-Dayton Bosnia and Herzegovina as a complex, segmented, and dysfunctional state.The subject of this paper is an analysis of the Dayton and post-Dayton conceptions of the administrative power of Bosnia and Herzegovina twenty five years since its establishment. The paper, using methods of qualitative analysis of legal acts, legal exegesis, as well ascomparative and axiological methods, and relying on the theories and conceptions of the distribution of competences in a complex state, seeks to present the Dayton and post-Dayton conceptions of the administrative power in Bosnia and Herzegovina from a twenty-five year distance. The basic research hypothesis is that states with complex organisational structure, such as Bosnia and Herzegovina, require decentralised organisational and material structures in the executive branch both from the aspect of functionality and economy and the aspect of their sustainability.
Keywords: Administrative power; Public administration; Dayton Peace Agreement; Transfer of jurisdiction; OHR; Bosnia and Herzegovina